Parametric study of supercritical carbon dioxide (sCO2) cycles for waste heat recovery from jet engines - Chong, Zhi Ken; Saadon, Syamimi (The Aeronautical and Astronautical Society of the Republic of China, 2022)
This study will focus on technologies and applications that have excelled in many other industries but yet to be applied in aviation, which is waste heat recovery technology with supercritical carbon dioxide (sCO2) as the cycle’s working fluid. In this case, this technology can help to reduce the jet engines’ fuel consumption, and minimize fuel expenses and also carbon dioxide (CO2) emissions. The analysis of sCO2 cycle that is thermodynamically integrated into a turbofan jet engine is conducted via simulation within the Aspen Plus software and the Microsoft Excel is used for the post-processing of the results. Moreover, a quantitative analysis is done to select the best performing sCO2 cycle configuration based on the jet engine’s performance increment after the cycle’s integration as its waste heat recovery system. All in all, the obtained results show that recuperation cycle (42.46%, 2197.67 kW) performs much better than basic Brayton cycle (18.53 %, 2555.84 kW) in terms of thermal efficiency and network. As for jet engine performance, integrating the basic Brayton cycle has generated greater thrust specific fuel consumption (TSFC) savings of 13.91% with improved value of 1.7474 kg/s/kN compared to the recuperation cycle savings of 7.06% and improved value of 1.8865 kg/s/kN.